Paciente femenino de 51 años de edad con diabetes mellitus tipo 2 y lesión tumoral benigna. - Medina Zapata, Anyeline Enedina (2020)
The present case is a 51-year-old female patient who lives in Babahoyo. She was diagnosed 15 years ago with Diabetes Mellitus type II, within the family pathological history, indicates that there is no history of Diabetes in her family, and 3 years ago she was diagnosed with a benign lumbar-sacral tumor. She says that in recent months she has felt bad, because of the pain that occurs in her legs due to the injury, since it involves nerves and arteries which make it difficult for blood to circulate. Take your Diabetes medication before breakfast and before snack. On physical examination, head and chest were unremarkable, normal heartbeat, ventilated lung fields. Nutritional Assessment was performed in which her BMI revealed a normal state, biochemical examinations revealed high glucose, for which she was referred to the nutritionist for her intervention. A diet plan is made considering the caloric needs of the patient, the diet will be a diabetic diet, low in saturated fat, high in fiber and will be divided into 5 times. Which includes breakfast, snack, lunch, snack and snack. This diet should be based on the consumption of fruits, vegetables, complex carbohydrates, dairy and skim derivatives, lean meats without fats or skin, preferably fish, chicken and turkey. Perform physical activity in case there is no impediment or pain in your lower extremities, in order to balance the patient's glucose levels. Follow-up and monitoring show improvement in the patient, her biochemical tests changed positively to her health condition, her glucose decreased.